Expression of Retinoid Acid Receptor-Responsive Genes in Rodent Models of Placental Pathology - Mocker, Alexander; Schmidt, Marius; Hübner, Hanna; Wachtveitl, Rainer; Cordasic, Nada; Menendez-Castro, Carlos; Hartner, Andrea; Fahlbusch, Fabian (International Journal of Molecular Sciences, 2019)
In humans, retinoic acid receptor responders (RARRES) have been shown to be altered in third trimester placentas complicated by the pathologies preeclampsia (PE) and PE with intrauterine growth restriction (IUGR). Currently, little is known about the role of placental Rarres in rodents. Therefore, we examined the localization and expression of Rarres1 and 2 in placentas obtained from a Wistar rat model of isocaloric maternal protein restriction (E18.5, IUGR-like features) and from an eNOS-knockout mouse model (E15 and E18.5, PE-like features). In both rodent models, Rarres1 and 2 were mainly localized in the placental spongiotrophoblast and giant cells. Their placental expression, as well as the expression of the Rarres2 receptor chemokine-like receptor 1 (CmklR1), was largely unaltered at the examined gestational ages in both animal models. Our results have shown that RARRES1 and 2 may have different expression and roles in human and rodent placentas, thereby underlining immanent limitations of comparative interspecies placentology. Further functional studies are required to elucidate the potential involvement of these proteins in early placentogenesis.
EVALuna2:209516